Comparative assessment of antibiotic self-medication practices among under-graduate medical students and general population - Mir, Shakeel Ahmad; Ahangar, Junaid; Shakeel, Danish (International Journal of Research in Medical Sciences, 2019)
Background: Self-medication with antibiotics is a global problem and increases the risk of antibiotic resistance which impacts morbidity and mortality. Methods: A total of 180 Medical students and the same number of people from general population were given a pre-validated questionnaire. The total respondents were 168 among general population and 173 among medical students. Results: 21.42% respondents from general population and 82.08% medical students practiced antibiotic self-medication. 66.66% respondents from general population practiced antibiotic self- medication to save time and money. 57.04% medical students had previous experience of treating similar symptoms.83.33% respondents from general population and 89.43% medical students used antibiotics to treat fever, cough, cold, sore throat and similar symptoms. 50.00% respondents from general population consulted the chemist/pharmacist before using the antibiotics.38.02% students consulted their textbooks for drug information. Only 16.66% respondents from general population and 24.64% students continued the antibiotics till full recovery. Conclusions: Antibiotic self- medication is more prevalent among medical students as compared to general population. Medical students need to be targeted repeatedly during their education and be taught the value of using antibiotics with caution. Public awareness and strict enforcement of law to control the sale of antibiotics without a valid prescription are needed to minimize antibiotic self- medication and associated risks.